Simulating the entire progressive failure process of rock slopes using the combined finite-discrete element method - Sun, Lei; Liu, Quansheng; Abdelaziz, Aly; Tang, Xuhai; Grasselli, Giovanni (Computers and geotechnics, 2022)
This paper presents a novel approach (Y-slope) to simulate entire slope failure processes, from initiation, transport to deposition. The algorithm is implemented in a combined finite-discrete element method code. Absorbing boundary conditions are implemented to improve computational efficiency for the initial stress state equilibrium. Strength reduction methods, considering both tensile and shear failure modes, are implemented to evaluate the slope stability, where the safety factor and critical failure surface are automatically obtained. The energy dissipation mechanism, due to blocks’ friction and collision, is incorporated to accurately simulate the block kinematics during the post-failure stage. The accuracy and robustness of Y-slope are validated by numerical tests, and the failure mechanism and failure progress of a homogeneous and jointed rock slope are presented. Results indicate that Y-slope can not only evaluate the slope stability state (e.g., safety factor and critical failure surface), but also simulate the entire failure process (e.g., slope deformation, failure surface evolution, block transport and deposition). In addition, the critical role of existing discontinuities on the slope stability and failure mechanism are also highlighted. This work proposes a promising tool in understanding the failure mechanism and assessing the potential risk by predicting the entire failure process of rock slopes.